Improving Tenth Graders’ English Listening Skills Through Podcast-Based Teaching at Senior High School - Puteri, Femanda Rizqy Permata; Ni'mah, Fauziyatun (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The title of this research is The Effect of Using Podcasts as a Learning Media to Improve English Listening Skills of Tenth Graders at SMA Assádah Bungah. The problem of this research is to determine the significance of the effect of using podcasts in teaching listening for tenth graders at SMA Assaádah Bungah. The aim is to find out whether podcast media is effective in teaching listening for tenth graders of SMA Assaádah. The researcher used a quantitative method using a quasi-experimental research design. To collect data, this research used pre-test, treatment, and post-test as instruments, and the data were collected, processed, and the results were compared using a statistical test result table using the SPSS 26.0 application. The population and sample of this research were 20% of tenth graders at SMA Assaádah in the 2024-2025 academic year totaling 66 students. The results of this research indicate that the use of podcasts as a listening learning media can improve students' listening skills effectively, as evidenced by the t-test formula.